Hemodynamic coherence in sepsis. Issue 4 (December 2016) - Morelli, Andrea; Passariello, Maurizio
Abstract : Microvascular alterations are a hallmark of sepsis and play a crucial role in its pathophysiology. Such alterations are the result of overwhelming inflammation, which negatively affects all the components of the microcirculation. As the severity of microvascular alterations is associated with organ dysfunction and mortality, several strategies have been tested for improving microcirculation. Nevertheless, they are mainly based on the conventional manipulation of systemic hemodynamics to increase the total flow to the organs and tissues. Other therapeutic interventions are still being investigated. In this review, we discuss the pathophysiology of septic microcirculatory dysfunction and its implications for possible treatments.